(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Klebsiella pneumonia is an opportunistic pathogen causes several diseases including sepsis, pneumonia, and wound infections. There are two pathotypes of Klebsiella pneumonia: classical K. pneumoniae (cKp) and hypervirulent K. pneumonia (hvkp), which is an emerging variant of (ckp), clinically distinguished by invasive and multiple site infections. A total of 150 samples were collected from different hospitals in Kirkuk city during the period between November 2021 to June 2022. The age of patients ranged between (20– 60) years old of both sexes. These samples were highly recovered from females with a rate 66.67% compared to the males 33.33%. Thirty (20%) K. pneumonia was recovered from different clinical specimens including urine, sputum, burn and wound swabs. The most common age group infected with K. pneumoniae was (20-40) with a rate of 63.33% and commonly recovered from inpatients 53.33% rather than outpatients (46.67%). The capability of K. pneumonie isolates to form biofilm was also examined by using tissue culture plate (TCP) and Congo red agar (CRA) methods. The results indicate that biofilm production by TCP method was 70% (46.67% strong biofilm producer, 23.33 % moderate and 30 were negative), while Congo red agar (CRA) method showed 60% positivity for biofilm and 40% was negative. Antibiotic susceptibility test was conducted to all isolates by using disc diffusion test towards 8 antimicrobial agents. Klebsiella pneumoniae isolates showed multiple resistance against 3 or more of different antibiotic groups (gentamicin 93%, ampicillin 96%, amoxicillin –clavulanate 90%, cefotaxime 83%, ceftazidime 96%, meropenem 36%, levofloxacin 76 % and gentamicin 93 %. K. pneumoniae isolated from inpatients and from sputum samples were more resistant to antibiotics.